O grotesco na arte feminina contemporânea: Ana Mendieta - Permonian, Ariane Cristina Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
This research is a case study about the life and work of artist Ana Mendieta. Starting from a classical reading of grotesque aesthetics, strongly present in the artist's work, heading towards a research on contemporary art about performace and video art, based on the time when the artist produced her works and focusing on the use and exploration of the famale body in art. There is a relationship between art and politics demonstrating how the artist's communist and feminist ideologies were extremely influential in the creation of her works. The study ends after reading the work series of Super-8 by Mendieta, where all the aspects mentioned are used to analyze them.

Esta pesquisa se trata de um estudo de caso sobre a vida e obra da artista Ana Mendieta. Partindo de uma leitura clássica da estética grotesca, presente fortemente nas obras da referida, rumando para uma pesquisa na arte contemporânea sobre performance e videoarte, tendo como base a época em que a artista produziu suas obras e focando na questão da utilização e exploração do corpo feminino na arte. Há uma relação entre arte e política demonstrando como as ideologias comunista e feminista da artista foram extremamente influentes para a criação de suas obras. O estudo finaliza após a leitura da série de obras em Super-8 de Mendieta onde todos os aspectos citados são utilizados para analisá-las.
The grotesque in contemporary feminine art: Ana Mendieta
Keywords: Grotesque; Feminism; Video art; Ana Mendieta; Performance; Grotesco; Feminismo; Videoarte